RNA-directed RNA polymerase3 from Nicotiana attenuata is required for competitive growth in natural environments - Pandey, Shree Prakash; Gaquerel, Emmanuel; Gase, Klaus; Baldwin, Ian T. (Plant physiology, 2008)
SDE1/SGS2/RdR6, a putative RNA-directed RNA polymerase, maintains plant defenses against viruses in Arabidopsis (Arabidopsis thaliana) and Nicotiana benthamiana, but its function has not been examined in natural habitats or with respect to other ecological stresses. We evaluated the organismic-level function of this gene (NaRdR3) in an ecological model species, Nicotiana attenuata, by transforming plants to stably silence RdR3 (irRdR3). Minor morphological changes (elongated leaves and reduced leaf number) and increased susceptibility to tobamoviruses typical of RdR6 silencing in other species were observed, but these changes did not alter the reproductive performance of singly grown plants (measured as seed and capsule production) or herbivore resistance in laboratory trials. 454-sequencing of irRdR3's small RNA (smRNA) transcriptome revealed that 21- and 24-nucleotide smRNAs were not affected, but the abundance of 22- to 23-nucleotide smRNAs was reduced. When planted in pairs with wild-type plants in N. attenuata's natural habitat in the Great Basin Desert, irRdR3 plants produced shorter stalks with significantly reduced flower and capsule numbers, but did not influence the ability of plants to resist the native herbivore community, indicating that silencing RdR3 reduced a plant's competitive ability. We tested this hypothesis in the glasshouse by planting irRdR3 and wild-type pairs in communal containers; again irRdR3 plants had severely reduced stalk elongation and reproductive measures. The reduced competitive ability of irRdR3 plants was associated with altered phytohormone homeostasis, especially as reflected in the distribution of auxin. We suggest that RdR3 helps to regulate hormone balance when plants compete with conspecifics in natural environments.